2008
DOI: 10.1002/anie.200703928
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oxidation of Methane to Methanol at Low Temperature and Pressure in an Electrochemical Fuel Cell

Abstract: Fuel for thought? The direct oxidation of methane to methanol occurs at atmospheric pressure between 50 and 250 °C in a fuel‐cell‐type reactor (see picture). The efficiency of the electrochemical activation of oxygen is higher than that for the catalytic activation of oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 21 publications
1
61
0
4
Order By: Relevance
“…at intermediate temperatures (373-573 K) [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Hibino et al reported that SnP 2 O 7 and Sn 0.9 In 0.1-P 2 O 7 exhibit high protonic conductivities of above 10 − 2 S cm − 1 from 348 to 573 K and above 10 − 1 S cm − 1 from 398 to 573 K under unhumidified conditions, respectively [7,8].…”
Section: Introductionmentioning
confidence: 96%
“…at intermediate temperatures (373-573 K) [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Hibino et al reported that SnP 2 O 7 and Sn 0.9 In 0.1-P 2 O 7 exhibit high protonic conductivities of above 10 − 2 S cm − 1 from 348 to 573 K and above 10 − 1 S cm − 1 from 398 to 573 K under unhumidified conditions, respectively [7,8].…”
Section: Introductionmentioning
confidence: 96%
“…Nagao et al reported that the conductivities of AP 2 O 7 (A = Sn, Ti, Ge, Si) increased in the order of Ge 4+ < Si 4+ < Ti 4+ < Sn 4+ in unhumidified air [9], and that proton-conducting Sn 1−x R x P 2 O 7 (R = Al 3+ , In 3+ ) were also applied to some electrochemical reactors, such as H 2 /air fuel cell, selective catalytic reduction of NO x , direct oxidation of methane to methanol, and gas sensors, etc. [13][14][15][16][17][18]. Chen et al reported that Sn 0.9 In 0.1 P 2 O 7 can conduct both protons and oxide-ions in the temperature range from 403 to 503 K [19].…”
Section: Introductionmentioning
confidence: 98%
“…Previously, a number of catalytic systems have also been developed for methane oxidation. [12][13][14][15] They all function at high temperatures and several are heterogeneous systems operating in zeolites. [16][17][18] Our biomimetic tricopper complex oxidizes methane efficiently at room temperature and can be formulated either as a homogeneous or heterogeneous catalyst.…”
mentioning
confidence: 99%